MODEL-MODEL PENILAIAN SEKURITAS - Rosyadi, Imron (Universitas Muhammadiyah Surakarta, 2004)
The valuation of securities is very important, it caused by the target of financial management thatwas to maximize the wealth of stockholder by means of maximize value of the firm. In this article, thewriter showed the valuation models of securities such as, obligation, common stock, and preference stock.The obligation value is present value from annuity (payment of fixed interest rate each period) andadded by present value of principal loan. Whereas in valuation of stock, at least there are fourvaluation model of common stocks; they are: constant growth model, one step growth model, two stepsgrowth model, three steps growth model. The valuation of preference stock principally is equal with thevaluation of obligation, where division of dividend is consistent.